An Atlas of Anatomy - John Charles Boileau Grant 1886-1973 (USA Williams & Wilkins company, 1973)
International Student Edition
1. Upper limb, abdomen, perineum, pelvis, and lower limb.--II. Vertebrae and vertebral column, thorax, head and neck
Keywords: Applied Sciences (3GdYdhe GdJWHjbjIs; General -- Atlases; Human anatomy; Anatomy